Pengaruh Kepribadian Terhadap Kepuasan Kerja Karyawan Starwood Furniture Indonesia - Dwi Agung Nugroho Arianto; Abdul Choliq A (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2019)
This study aims to re-examine the influence of personality on employee job satisfaction because there are several researchers who provide different opinions or research results, then to determine the effect of personality on job satisfaction of employees of PT. Starwood Furniture Indonesia. The data used in this study are primary data obtained from the results of distributing questionnaires to employees and secondary data taken directly from the data that has been recorded or documentation at PT. Starwood Furniture Indonesia. The analysis method in this study uses simple regression. This study found results that personality significantly influence employee job satisfaction.